Editorial - Oniwide, Oyetola Olaoluwa (NIU Journal of Humanities; Vol 9 No 2 (2024): NIU Journal of Humanities, Vol. 9 No. 2, June 2024, 2024)
This issue of NIU Journal of Humanities touches on Development Administration, Educational Psychology, Climate Change, Social Philosophy as well as Language and Literary Studies. The first part of the Journal focuses on Development Administration. Using the Fiscal Federalism of Nigeria as a case study, one of the papers in this section empirically identifies the major challenges proterty tax and fiscal federalism to include: centralization at the state level, the absence of a comprehensive database, tax evasion, legal exemptions, skill shortages, lack of political will, and corruption. The paper recommends, amongst others, that the state government should states to relinquish the unconstitutional centralization of property tax functions and empowering local governments for independent assessment and collection. One of the papers, in the second section on Educational Psychology, argues that moral education as a means of regenerating social norms and moral values.  It is revealed in the paper, among other things, that job decision latitude was the main contributor to the prediction of burnout of academic staff of public universities and that university academic staff members are not immune to burnout and other-work related challenges affecting workers generally.  It is therefore, recommended that Government, university administrator and university management should improve on university work environment by providing necessary facilities that will enhance favourable work environment. This in turn will reduce the level of burnout among the university academic staff. In the third section on Climate Change, one of the papers reveals that temperature and precipitation affected soil moisture and organic matter from 1996-2016 and recommends the application of organic materials on soil to increase organic matter content and the practise of mulching will also conserve soil moisture. One of the papers, in the fourth section on Social Philosophy, examines those cultural practices in the bible that are similar to African cuture. These biblical practices are juxtaposed with similar African cultural practices in order to better illustrate the teaching of the Bible to the Africans with the tool of “inculturation hermeneutics” for the exegetes. Papers in the last section deals with issues in Language and Literary Studies. Several lierary works are examine in order to provide a useful contribution to how different worldview unites and differs in the human search to unravel 'truth'. On the whole, this issue of NIU Journal of Humanities features many empirical and theoretical based articles which can be of great benefit to every reader.